Identifikasi Postur Kerja pada Karyawan Sriwijaya Motor dalam Penerapan Metode RULA - Ali, Dimas Nur; Septianto, Farras (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
Sriwijaya Motor is a motorbike repair shop that provides motorbike services, tune ups, bore ups, and also sells various motorbike spare parts. Working conditions that threaten the safety and health of employees are considered dangerous. Fatigue or problems with the musculoskeletal system or muscles, such as body aches during work or after work, and muscle aches, are signs of danger to worker safety and health. As work is performed in inappropriate postures repeatedly, employees complain about inappropriate work postures. Most of the work is done manually, violating ergonomic rules. This research aims to determine employee work posture using the Rapid Upper Limb Assessment (RULA) method. The results show that one of the employees from Sriwijaya Motor who was evaluated using the RULA method got a final score of 4, this shows that their attitude towards their work is in the low risk category, only action is needed to improve their work position in the future. Keywords: Ergonomics, Final Score, Risk, RULA, Work Posture